Analisis Penerapan Alat Pemadam Api Ringan (APAR) Di PT. X Pekalongan - Luthfan Firdani; - Ekawati; Bina Kurniawan (Jurnal Kesehatan Masyarakat (Undip), 2014)
PT. X Pekalongan is a company that runs in the textile industry, in June 2013 the company got burned. According to the information from employees, the loss because of that fire could be minimized if 25 fire extinguishers were not broke and could be used well.  The purpose of this study is to analyze the application of fire extinguisher at PT. X Pekalongan. The study is using descriptive approach method to describe a situation in an objective way. The method used is descriptive surveys and interviews with observational approach. The results of the 44 fire extinguishers found in the plant area is known that the level of conformity in the application of fire extinguishers companiy already have the 50.2% adjustability and 49.8% discrepancy rate. The discrepancy of fire extinguisher there were position, position sign, height and distance between fire extinguisher. The company is also still less attention for the APAR damage and inspection not been continuously yet.  There were some fire extinguisher that not had the used direction,  there is no protection to easy take off of fire extinguisher. Inspection records was not available yet. Companies should more attention about application of fire extinguisher and organize training for fire extinguisher application or fire prevention training for all employees